2019
DOI: 10.3390/mi10120837
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Time-Delay Valve Mechanism on Paper-Based Devices for Automated Competitive ELISA

Abstract: Paper-based technologies have been drawing increasing attentions in the biosensor field due to their economical, ecofriendly, and easy-to-fabricate features. In this paper, we present a time-delay valve mechanism to automate a series of procedures for conducting competitive enzyme-linked immunosorbent assay (ELISA) on a paper-based device. The mechanism employs a controllable time-delay valve, which has surfactants to dissolve the hydrophobic barriers, in a fluid pathway. The valves can regulate the liquid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, implementing these valves in wearable sensors made of paper would require adding electrical actuators and circuitry to the design, which would increase the complexity of the fabrication process. Chemically actuated valves that open upon the addition of organic solvents or surfactants have also been reported. However, organic solvents need to be dispensed manually.…”
Section: Introductionmentioning
confidence: 99%
“…However, implementing these valves in wearable sensors made of paper would require adding electrical actuators and circuitry to the design, which would increase the complexity of the fabrication process. Chemically actuated valves that open upon the addition of organic solvents or surfactants have also been reported. However, organic solvents need to be dispensed manually.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolvable materials have been utilized to delay flow on μPADs, such as pullulan film, surfactant, wax, and sugar . Yager et al reported on the use of dissolvable sucrose on paper to create programmable flow delays to program automated multistep fluidic protocols .…”
Section: Introductionmentioning
confidence: 99%
“…21 Among these methods, colorimetry has been the most commonly used because it is simple, easy to operate, and meets the basic needs for on-site detection without complex equipment. 22 Although many colorimetric ELISA μPADs provide ease of use, rapidity, cost-effectiveness, and portability, only a few have been specifically designed for detecting small targets, 23,24 particularly in relation to monitoring AFB 1 content using competitive ELISA. 25 Our group previously developed the first automated sandwich ELISA for an inkjet-printed μPAD.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color formed in the detection zone vs. nitrate or nitrite concentration. References [ 46 , 47 , 49 , 59 , 60 ].…”
mentioning
confidence: 99%